Tinjauan Pembangkit Hidrotermis Setelah Penggabungan PLTA Pompa Pada Sistem Tenaga Listrik Jawa-Madura-Bali - Multi, Abdul (Rekayasa Teknologi, 2011)
With the pumped storage integrated to the power system, an analysis of its schedulingis needed. The study is in the electrical power system related to hydrothermal units in thepower system of Jawa-Madura-Bali (JAMALI).The scheduling is based on the daily loadcurve and load distribution among hydrothermal units. With pumped storage operated, theload flow will influence the stability of power system. The objective of thermal unitsoptimization is to minimize total operation costs. Scheduling of pumped storage and optimization of thermal units are used a particleswarm optimization (PSO) technique due to its high-performance and flexibility. PSO isused as base algorithm to search for better solution. In addition power balance, waterdischarge and reservoir volume are considered. For the necessity of analysing it needs tosimulate in forcasting load of short term, scheduling pumped storage operation,computing load flow and minimising generation costs in the power system of JAMALI.